FRI0029 The Impact of Very Early Treatment on Patient Reported Outcomes in Rheumatoid Arthritis. (10th June 2014) - Basu, N.; Brock, F.
Abstract : Background: Despite substantial advances in the treatment of rheumatoid arthritis (RA), patients continue to report long term limitations. The combination of TNFα antagonists and methotrexate (MTX) in early RA (ERA), defined as disease of >4-24 months duration, improves both clinical and patient reported outcomes. Similar intensive treatment of patients with very early RA (VERA), defined as disease of ≤4 months duration, is known to improve clinical outcomes even further. It is however less clear if very early treatment results in greater gains in patient reported outcomes (PRO). Objectives: We investigated whether patients who received TNFα antagonist and MTX combination therapy within 4 months of diagnosis benefited in terms of longer term quality of life (QOL), mental health and disability compared to those who waited (>4-24 months) to receive such treatment. Methods: A post-hoc analysis of the Combination of MTX and Etanercept (ETN) in active early rheumatoid arthritis trial (COMET) 1 was undertaken. Those subjects receiving MTX and ETN were analysed according to baseline disease duration (VERA v ERA) for the differences in their PROs: QOL (SF36), pain (visual analogue scale, VAS), fatigue (VAS), disability index (HAQ-DI), anxiety & depression (Hospital Anxiety & Depression scale, HADS-A & HADS-D). Baseline differences between all VERA and ERA subjects were identified using ANOVA, Mann-Whitney and Chi-squared tests as appropriate and subsequently used as covariates within ANCOVA models which were performed to compare PRO responses at week 52 among those receiving MTX and ETN combination therapy. Summary scores are presented as Least Squares mean[SE] unless otherwise stated, and a p≤0.05 is considered statistically significant. Results: VERA subjects were more likely to be smokers compared to ERA subjects, but otherwise there were no significant differences in baseline characteristics. Of those receiving combination therapy (VERA: n=63, mean[sd] disease duration 3.6[0.5] months; ERA: n=157, disease duration 10.7[5.4] months), there were no statistically significant differences in week 52 PROs according to baseline disease duration (VERA v ERA: SF36 physical summary 43.9[1.2] v 44.3[0.9]; SF36 mental summary mean 51.2[1.3] v 48.6[0.9]; pain VAS 20.5[3.1] v 20.7[2.2]; fatigue VAS 26.3[3.3] v 29.0[2.3]; HAQ 0.6[0.07] v 0.6[0.05] and HADS-A 4.8[0.5] v 5.5[0.3]), although there was a modest, non-significant, indication that VERA subjects were less depressed (HADS-D 3.6[0.5] v 4.6[0.3], p=0.09). Conclusions: Unlike clinical outcome measures, very early treatment with the combination of TNFα antagonists and methotrexate does not appear to improve PROs compared to those who receive this treatment after a longer disease duration. Since symptoms such as pain and fatigue commonly precede diagnosis by several months, it may be that the "window of opportunity" for generating the greatest improvements in PROs is even earlier, when they are typically harder to target. References: Emery et al. Comparison of methotrexate monotherapy with a combination of methotrexate and etanercept in active, early, moderate to severe rheumatid arthritis (COMET): a randomised, double-blind, parallel treatment trial. Lancet 2008;372:375-82. Acknowledgements: The COMET investigators, Pfizer & Laraine Aikman Disclosure of Interest: N. Basu Grant/research support: Pfizer, GSK, Consultant for: MSD, GSK, Pfizer, Speakers bureau: Sanofi Aventis, Pfizer, F. Brock Consultant for: Pfizer DOI: 10.1136/annrheumdis-2014-eular.2402